Time trend and causes of HIV/AIDS mortality in the state of Santa Catarina, 2010–2019 - Escobar, Braulio Sambaquy Escobar; Cunga, Ilda Vaica Armando Cunga; Parma, Gabriel Oscar Cremona Parma; Iser, Betine Pinto Moehlecke Iser; Schuelter-Trevisol, Fabiana (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Although the acquired immunodeficiency syndrome (AIDS) has no cure, antiretroviral treatment has considerably increased the survival of people living with the disease or with the human immunodeficiency virus (HIV), reducing the incidence of opportunistic infections in these patients. Thus, this treatment changed mortality rates and diversified the causes of death, including reasons related to increased longevity, such as chronic non-communicable diseases, common in the uninfected population. Therefore, the current epidemiological transition motivated us to study the death profile of people with HIV/AIDS in the state of Santa Catarina. Objective: To investigate case characteristics, as well as the time trend and distribution of deaths, among people with HIV/AIDS in Santa Catarina between 2010 and 2019. Methods: In this ecological, epidemiological study, we consulted all death records from the Santa Catarina Mortality Information System that had HIV/AIDS among the causes and occurred between 2010 and 2019. Results: A total of 5,174 death records were analyzed. In the period, the mean mortality rate among people with HIV/AIDS was 7.64 deaths per 100 thousand inhabitants (95% confidence interval — 95%CI 6.61–8.67) — 8.99 in 2010 and 6.06 in 2019 —, showing a downward trend of 0.38% per year. Conclusion: We identified a downward trend in mortality. Deaths were concentrated on the coast, in more populous cities. Furthermore, the finding of improper completion of the death certificate points to the need to invest in improving the training of professionals responsible for this document.